Testing for complete pass-through of exchange rate without trade barriers - Zhang, Tengfei; Li , Tianxiang; Baležentis, Tomas; Štreimikienė, Dalia (Journal of Business Economics and Management, 2020)
The objective of this paper is to test whether the complete pass-through of exchange rate exists when there are almost no transaction costs and in the environment of competitive market. In general, the literature claims that the pass-through of exchange rate is incomplete due to imperfect market, i.e. the presence of transaction costs and imperfect competition. The quasi-experimental case of the food import to Hong Kong from Mainland China is considered in the analysis. The results show that the pass-through of the exchange rate of Chinese RMB against to US dollar to Hong Kong’s food import price is complete in long-run equilibrium. Besides, the short-run adjustment significantly contributes to correcting the deviation from the long-run pass-through effect. Moreover, the complete pass-through still exists after accounting for the effects of asymmetry and volatility. Therefore, this paper contributes to the literature by providing empirical evidence that the complete pass-through of exchange rate can exist in the real world.